Cascade Upgrading of Biomass-Derived Furfural to γ-Valerolactone Over Zr/Hf-Based Catalysts - Sun, Wenjuan; Li, Haifeng; Wang, Xiaochen; Liu, Anqiu (Frontiers in Chemistry, 2022)
Biomass feedstocks are promising candidates of renewable clean energy. The development and utilization of biological energy is in line with the concept of sustainable development and circular economy. As an important platform chemical, γ-valerolactone (GVL) is often used as green solvent and biofuel additive. Regarding this, the efficient synthesis of GVL from biomass derivative furfural (FF) has attracted wide attention recently , However, suitable catalyst with appropriate acid-base sites is required due to the complex reaction progress. In this Mini Review, the research progress of catalytic synthesis of GVL from furfural by Zr/Hf-based catalysts was reviewed. The different effects of Lewis acid-base and Brønsted acid sites in the catalysts on each steps in the reaction process were discussed firstly. Then the effects of regulation of acid-base sites in the catalysts was also studied. Finally, the advantages and challenges of Zr/Hf-based catalysts in FF converted to GVL system were proposed.